018 DT-CMR imaging of deranged microstructure in situs inversus totalis. (3rd April 2017) - Khalique, Z; Ferreira, PF; Scott, AD; Nielles-Vallespin, S; Firmin, DN; Pennell, DJ
Abstract : Background: Diffusion tensor cardiovascular magnetic resonance (DT-CMR) is a non-invasive technique that has been histologically validated to provide information on the microstructure of the myocardium. 1–3 There is a standard helical myocyte arrangement in the situs solitus (SS) heart, as viewed from the apex; left-handed in the epicardium, circumferential in the mesocardium and right-handed in the endocardium. This generates the opposing basal clockwise rotation and apical anticlockwise rotation necessary for torsion. 4 However in situs inversus totalis (SIT) there is mirror image arrangement of the visceral organs. There are no histological studies assessing how myocardial microstructure is affected in SIT. DT-CMR offers a unique opportunity to evaluate the microstructural abnormalities in SIT. Methods: 12 SIT patients and 12 matched healthy volunteers were scanned in a 3T Siemens Skyra scanner. DT-CMR was performed at peak systole in the short axis at base, mid and apex. 2 people had whole heart tractography. A STEAM sequence with bmain=600 s/mm 2 and bref=150 s/mm 2 was used, as previously described. 3 Strain and torsion assessment was performed using DENSE5. Results: Patients were age and sex-matched (SIT 39.5 and SS 34.5 years, 3/12 male). Myocyte organisation at base, mid and apex was significantly different in SIT hearts compared to the SS hearts. Figure 1 shows example tractography. In SS, the endocardial positive helix angle (HA) progressed to a negative HA in the epicardium. In SIT hearts this pattern was inverted at the base and approached normal at the apex, with a mid-ventricular transition zone. Mid-ventricular peak radial and circumferential strain were reduced in SIT (0.4±0.16 vs 0.56±0.16, p=0.02, and −0.16±0.02 vs −0.18±0.01 p=0.04 respectively). Peak absolute torsion was reduced in SIT 3.6° [3.6°] vs 8.0° [3.5°]. Conclusion: This is the first human DT-CMR study of SIT hearts. We demonstrate that the SIT heart has an inverted myocyte orientation at the base that approaches normal towards the apex. Peak absolute torsion is reduced. Peak radial and circumferential strain are also reduced at the mid-ventricle. The deranged microstructure in SIT has functional effects, the long-term outcomes of which require further study. References: . Reese TG, Weisskoff RM, Smith RN, et al . Imaging myocardial fibre architecture in vivo with magnetic resonance. Magn Reson Med 1995;34(6):786–791. Scollan DF, Holmes A, Winslow R, et al . Histological validation of myocardial microstructure obtained from diffusion tensor magnetic resonance imaging. Am J Physiol Heart Circ Physiol 1998;275(6):H2308–H2318. Nielles-Vallespin S, Khalique Z, Ferreira PF, et al. Assessment of Myocardial Microstructural Dynamics by In Vivo Diffusion Tensor Cardiac Magnetic Resonance. J Am Coll Cardiol 2017;69(6):661–676. SenguptaPP, Tajik AJ, Chandrasekaran K, et al . Twist Mechanics of the Left Ventricle: Principles and Application. JACC: Cardiovascular Imaging 2008;1(3):366– 376. Scott AD, Tayal U, Nielles-Vallespin S, et al . Accelerating cine DENSE using a zonal excitation. J Cardiov Magn Reson 2016;18(1):O50.